From musk to body odor: Decoding olfaction through genetic variation. - Bingjie Li; Marissa L Kamarck; Qianqian Peng; Fei-Ling Lim; Andreas Keller; Monique A M Smeets; Joel D Mainland; Sijia Wang (PLoS Genetics)
The olfactory system combines input from multiple receptor types to represent odor information, but there are few explicit examples relating olfactory receptor (OR) activity patterns to odor perception. To uncover these relationships, we performed genome-wide scans on odor-perception phenotypes for ten odors in 1000 Han Chinese and validated results for six of these odors in an ethnically diverse population (n = 364). In both populations, consistent with previous studies, we replicated three previously reported associations (β-ionone/OR5A1, androstenone/OR7D4, cis-3-hexen-1-ol/OR2J3 LD-band), but not for odors containing aldehydes, suggesting that olfactory phenotype/genotype studies are robust across populations. Two novel associations between an OR and odor perception contribute to our understanding of olfactory coding. First, we found a SNP in OR51B2 that associated with trans-3-methyl-2-hexenoic acid, a key component of human underarm odor. Second, we found two linked SNPs associated with the musk Galaxolide in a novel musk receptor, OR4D6, which is also the first human OR shown to drive specific anosmia to a musk compound. We noticed that SNPs detected for odor intensity were enriched with amino acid substitutions, implying functional changes of odor receptors. Furthermore, we also found that the derived alleles of the SNPs tend to be associated with reduced odor intensity, supporting the hypothesis that the primate olfactory gene repertoire has degenerated over time. This study provides information about coding for human body odor, and gives us insight into broader mechanisms of olfactory coding, such as how differential OR activation can converge on a similar percept.